Vitamin D metabolites in synovial fluid. Issue 5 (May 1987) - Fairney, A; Straffen, A M; May, C; Seifert, M H
Abstract : This study has shown that it is possible to measure vitamin D metabolites and vitamin D binding protein (DBP) in synovial fluid as well as serum. Significant amounts of 25-OHD, 24, 25-(OH)2D, and DBP are present in synovial fluid. The 25-OHD and DBP maintain a serum:synovial fluid ratio of approximately 2:1 irrespective of the type of joint disease, whereas no such relationship was detected for 24, 25-(OH)2D. The possible reasons for these findings are diffusion of the metabolites into synovial fluid or local production from suitable precursors, or both.